Islam Nusantara Dan Apresiasi Atas Kebudayaan Lokal - Putra, Andi Eka (AL-ADYAN, 2020)
Islamic thought in the last several decades of Indonesia has been dynamic. As such is evidenced by the emergence of some new terms related to Indonesian Islam, such as modernist Muslim, trans-formative Islam, Islamic postmodernism, Indigenous Islam, and Nusantara Islam (Islam of the archipelago). These terms constitute an idea of thoughts largely promoted by Nahdlatul Ulama, or NU (the largest organization of traditionalist Muslim in Indonesia and elsewhere), especially among its younger generation. As a form of thoughts, they are considered fine. Yet, many groups of Muslim have objected them, arguing that they may become a new  form of “school of Islam” (madzhab). Nusantara Islam, in principle, promotes the values of tolerance and humanism, and recognizes local expressions of culture and beliefs, specific to the archipelago. This characteristic of Nusantara Islam is not dissimilar with that of the NU, that is, celebrating local tradition as a locus teologicus.  Thus, the emergence of Nusantara Islam discourse has become a heated debate in Muslim public, because of its inclusive style and its opposition with the so-called ‘Arabized Islam’.